Komunikasi Antar Budaya Etnis Tiong Hoa, Melayu, dan Dayak dalam Menjaga Toleransi Antar Etnis di Singkawang - Violita, Jessica; Paramita, Sinta (Koneksi, 2025)
The object of this research is intercultural communication that occurs among a group of Chinese, Dayak and Malay communities in Singkawang. At first, Singkawang was not a city but a village part of the Sambas Sultanate area as a stopover for traders and gold miners from the Monterado area which is now a sub-district in Bengkayang Regency which is located to the east of Singkawang. With cultural diversity consisting of 3 majority ethnicities, namely Dayak, Chinese and Malay. The city of Singkawang, West Kalimantan, is in first place as the most tolerant city in Indonesia according to SETARA Institude, this is because of the harmonious life of its diverse society. This research uses qualitative research methods which aim to determine social interactions between Chinese, Dayak and Malay communities in Singkawang, West Kalimantan. Based on the Singkawang Central Statistics Agency, the area of Singkawang city is around 504 square kilometers with a population of 235,064 people in Singkawang. Based on population data from the West Kalimantan provincial government in 2023, there are 235,064 people in the city of Singkawang. Objek dalam penelitian ini adalah komunikasi antar budaya yang terjadi kepada sekompok masyarakat Tionghoa, Dayak, dan Melayu di Singkawang. Pada awalnya, Singkawang bukanlah kota melainkan sebuah desa bagian dari wilayah Kesultanan Sambas sebagai tempat singgah para pedagang dan penambang emas dari daerah Monterado yang kini menjadi sebuah kecamatan di Kabupaten Bengkayang yang berada di sebelah Timur Singkawang. Dengan keberagaman budaya yang terdiri dari 3 etnis mayoritas yaitu etnis Dayak, Tionghoa dan Melayu. Kota Singkawang Kalimantan Barat menempati posisi pertama kota paling toleransi di indonesia versi SETARA Institude hal ini karena kehidupan harmonis masyarkatnya yang majemuk. Penelitian ini menggunakan metode penelitian kualitatif yang bertujuan untuk mengetahui interaksi sosial antara masyarakat Tionghoa, Dayak, dan Melayu di Singkawang, Kalimantan Barat. Berdasarkan Badan Pusat Stastik Singkawang, Luas kota Singkawang sekitar 504 kilometer persegi dengan jumlah penduduk Singkawang sebanyak 235.064 jiwa. Berdasarkan data kependudukan pemerintahan provinsi kalimantan barat tahun 2023 terdapat 235.064 jiwa dikota singkawang.